Preliminary results of a phase I, first-in-human, dose escalation study of IMM2902 in patients with HER2-expressing advanced solid tumors - Zhang, Jian; Zhao, Chuanhua; Cheng, Ying; Zhu, Liming; Song, Zhengbo; Xu, Nong; Wang, Zhen; Wang, Yanping; Du, Yiqun; Jing, Deqiang; Chen, Dinglu; Qu, Qiaofeng; et al. (Journal of clinical oncology, 2023)
e15185Background: IMM2902 is a novel recombinant bispecific fusion protein containing SIRPα binding domain trapped to the light chain of a humanized anti-HER2 antibody. With its high affinity to HER2 and CD47 on tumor cell membrane, IMM2902 can drive several anti-tumoral killing mechanisms such as directly targeting HER2 expressing tumor cells; restoring the phagocytic function of macrophages against tumor cells via CD47-SIRPα blockade; activating NK cells and macrophages mediated antibody-dependent cellular phagocytosis (ADCP) and antibody-dependent cellular cytotoxicity (ADCC); and most importantly, inducing accelerated HER2 internalization and degradation. Phase I dose escalation studies of IMM2902 in advanced solid tumors are conducted in both China and the United States, here we present the preliminary results from China trial. Methods: The dose escalation study of IMM2902 was conducted following a modified 3+3 design to evaluate the safety and tolerability of the study drug and to determine the MTD/RP2D. IMM2902 was administered intravenously every week (QW) in 4-week cycles, and the first cycle was the DLT observation period. The tumor responses were evaluated based on RECIST v1.1. IMM2902 pharmacokinetics (PK) and pharmacodynamics (PD) were also evaluated. Results: As of 26 December 2022, a total of 16 subjects had received at least one dose of IMM2902 in 5 dose cohorts (0.03, 0.1, 0.3, 0.9 and 2.0 mg/kg). Of the 16 subjects, no DLTs were observed. Treatment related adverse events (TRAEs) occurred in all 16 subjects (100%), with 4 subjects (25%) reported to have grade 3 TRAEs. No subject discontinued IMM2902 treatment due to TRAEs. The most common TRAEs were platelet count decreased (62.5%), infusion related reaction (50%), and anemia (43.8%). The most common grade 3 or above TRAE was platelet count decreased (18.8%). One SAE (grade 3 gastrointestinal hemorrhage) was reported, which was unrelated to IMM2902. Among 13 evaluable subjects, 4 patients achieved SD (2 pts with gastric cancer at 0.1 mg/kg, 1 pt with skin cancer at 0.9 mg/kg, and 1 pt with breast cancer at 2.0 mg/kg). Preliminary PK analysis showed IMM2902 had a non-linear PK. Serum concentration of IMM2902 reached steady state after the third administration. Preliminary PD data showed that, beginning at 0.3 mg/kg, the number of peripheral CD3+ and CD8+ T-cells increased after 4 weeks of treatment. Conclusions: IMM2902 showed an encouraging preliminary safety, tolerability and anti-tumor activity up to 2.0 mg/kg. The phase I/II study is ongoing. Clinical trial information: ChiCTR20212375.